Effects of fatigue on throwing performance in experienced team handball players - Nuno, A.; Chirosa, I. J.; van den Tillaar, R.; Guisado, R.; Martin, I.; Martinez, I.; Chirosa, L. J. (Journal of Human Kinetics, 2016)
The purpose of this study was to investigate the effect of central and peripheral physiological fatigue on throwing accuracy and ball release velocity in team handball. Twenty male subjects (age 24.7 ± 3.9 yrs, body mass 88.5 ± 5.0 kg, body height 1.86 ± 0.05 m, training experience 12.7 ± 3.8 yrs) from one handball team participated in this study. The participants completed four sets of eight laps of a circuit that consisted of specific team handball drills/exercises, with decreasing recovery times between the laps in each set in order to induce physiological fatigue. Duration of the recovery intervals determined the description of the effort made in each set: "light" (80 s recovery between laps), "moderate" (40 s), "hard" (20 s) and "very hard" (10 s). A heart rate, concentration of lactate in blood and the rate of perceived exertion (RPE) were recorded. Ball velocity and accuracy were measured after each set and they both decreased during a fatigue protocol. However, accuracy only decreased significantly in the end of the protocol, while ball release was already affected after the first round of the protocol. The results substantiate the initial hypothesis and confirm that both throwing accuracy and ball release velocity decrease significantly as physiological fatigue increases. These variables began to decrease when the fatigue quantification values were high or very high. The findings can be used by coaches to develop training programs to teach players how to identify fatigue thresholds and combat the effects of fatigue through decision-making skills at critical game moments.